Soluble model of Bose-atoms with two level internal structure: non-conventional Bose-Einstein condensation - Corgini, M.; Sankovich, D.P. (Condensed Matter Physics, 2010)
For a Bose atom system whose energy operator is diagonal in the so-called number operators and its ground state has an internal two-level structure with negative energies, exact expressions for the limit free canonical energy and pressure are obtained. The existence of non-conventional Bose-Einstein condensation has been also proved.